2019
DOI: 10.1186/s40352-019-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the implementation and sustainment of medication assisted treatment for opioid use disorders in prisons and jails

Abstract: BackgroundOpioid use disorder (OUD) is among the most prevalent medical condition experienced by incarcerated persons, yet medication assisted therapy (MAT) is uncommon. Four jail and prison systems partnered with researchers to document their adoption of MAT for incarcerated individuals with opioid use disorders (OUD) using their established treatment protocols. Employing the EPIS (Exploration, Planning, Implementation, and Sustainment) framework, programs report on systematic efforts to expand screening, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Consistent with prior research, we find that the availability of community‐based OAT treatment and the ability to link individuals to providers following release was a significant challenge [30,31]. In 2014, fewer than 5% of individuals referred to treatment upon release from the criminal legal system received OAT or naltrexone [32].…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with prior research, we find that the availability of community‐based OAT treatment and the ability to link individuals to providers following release was a significant challenge [30,31]. In 2014, fewer than 5% of individuals referred to treatment upon release from the criminal legal system received OAT or naltrexone [32].…”
Section: Discussionsupporting
confidence: 77%
“…Overall, lack of funds was the most frequently cited barrier to implementing all types of MOUD, either with regard to funding for medical staff or to cover cost of the medication, consistent with other studies of implementation of MOUD within correctional settings (Ferguson et al, 2019 ). However, unique issues were cited as barriers for each of the three types of medication.…”
Section: Discussionsupporting
confidence: 83%
“…Although this study identified the lack of funding as a significant barrier to the successful implementation of MOUD within state prison systems, recent federal funding initiatives provide potential resources. Yet, funding for additional resources, training, and education is not sufficient; critical to implementing MOUD within state prisons is a commitment to addressing the effects of the opioid crisis across leaders in criminal justice systems, health care, government, and community partners (Ferguson et al, 2019 ). Leaders across these systems can utilize the findings from the current study to advance policies to support the expansion of MOUD capacity to address the needs of individuals with OUD in state prisons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Group 1 likely had a lower access to addiction treatment, especially MOUD, while incarcerated, because the vast majority of prisons and jails did not offer access to MOUD at that time. Although improvements have been made more recently, there are still significant gaps in addiction care, including MOUD, during and after incarceration [ 33 , 34 ]. Regardless of the surrounding circumstances, an opioid-related overdose, which requires an emergency response by the police, represents a significant event within an individual’s life and could be seen as an opportunity for intervention and referral to treatment, thereby altering the untreated addiction trajectory.…”
Section: Limitationsmentioning
confidence: 99%